Does capital drain reduce total factor productivity growth in developing countries? - Yanikkaya, Halit; Altun, Abdullah (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
This study investigates the effects of foreign direct investment (FDI) and royalties and licence fees (RLF) on total factor productivity (TFP) growth of about 90 countries for the period 2003-2011 for both inward and outward variables. The estimates for the full sample indicate that while inward FDI stocks have no significant impact, outward FDI stocks reduce TFP growth. While none of the RLF measures have any significant effects, imports and exports have significantly positive effects on TFP growth for the full sample. Outward FDI stocks and RLF payments are estimated to have negative effects on TFP growth for developing nations. Moreover, both RLF receipts and payments are found to have a positive effect on TFP growth in developed nations. To stimulate TFP growth further, developing nations should improve their domestic business environments and find ways to keep investments at home
Argumenta Oeconomica, 2020, Nr 2 (45), s. 53-75
Keywords: capital drain; FDI; RLF; TFP